Desain Mekanisme Ballscrew untuk Retrofit Drilling axis Mesin Ficep H-Beam Drilling LFB-200-49 - Turnip, Kimar; Atmadi, Priyono; Novianto, Andreas Agung (ROTASI, 2021)
The retrofit process is the process of replacing or adding a component to a machine with the aim of adding value to the machine's performance. In this study, the retrofit process was applied to the replacement of the Ficep H-beam Drilling LFB-200-49 drilling machine axis. This retrofitting process requires a servo motor component as driving energy and a ballscrew to convert the motor rotation into a linear twist drill motion during the drilling process to replace the hydraulic system used previously. In the retrofit design carried out on the Ficep H-beam Drilling machine, the thrust generated by the hydraulic system is used as a reference to determine the dynamic load requirements that must be transmitted by the ballscrew while the thrust axial force from the drill bit is used as a reference in determining the power of the servo motor. In designing the replacement of the hydraulic system to this servo motor system, the recommended components are a ballscrew with a pitch of 10 mm and a ballscrew shaft diameter of 38 mm which meets the requirements for dynamic load transmission of 50,210.56 N and a servo motor with a power of 8.12 kW with the addition of a gear ratio of 3. : 1.